MALAY ETHNIC STRATEGY AGAINST MARGINALIZATION IN TANJUNG PUTUS VILLAGE LANGKAT REGENCY - Hapri Wannazemi; Hidayat Hidayat; Ibnu Hajar (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
This research aims to analyse the strategies of ethnic Malays in Tanjung Putus Village to face the marginalisation that has long occurred among ethnic Malays. The research method used was a qualitative method with a case study approach. Data collection techniques in this research used participant observation, in-depth interviews, and document study. data analysis using qualitative data analysis, namely data collection, data reduction, and data display. The results of the research carried out were that ethnic Malays in Tanjung Putus Village used a strategy to deal with marginalisation by increasing education for ethnic Malays who had at least a bachelor's degree in the hope of changing the stereotype paradigm of other ethnic groups in Tanjung Putus Village towards ethnic Malays and increasing the skills of ethnic Malays in the form of training. carried out periodically through villages and community service from state and private campuses in North Sumatra and improving health services for ethnic Malays who are considered underprivileged so they can afford treatment, as well as strengthening culture in the form of regional languages, traditional clothing, advice, and cultural traditions. Malay is used in various activities such as weddings, Langkat district birthdays, and national holidays, which are expected to strengthen the cultural values of the Malay ethnic group in Tanjung Village.